2017
DOI: 10.7727/wimj.2012.102
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Trauma and Dissociation in Patients with Obsessıve Compulsive Disorder

Abstract: Background and objective:The present study attempted to assess childhood trauma events and dissociative symptoms in patients with obsessive compulsive disorder (OCD). Method:The study included all patients who were admitted for the first time to the psychiatric outpatient unit over a 24-month period. Seventy-eight patients were diagnosed as having OCD during the twoyear study period. Childhood traumatic events were assessed with a Childhood Trauma Questionnaire (CTQ). Obsessive compulsive disorder symptoms wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…Psychological dissociation (assessed with DES) did not correlate with the outcome criteria of therapeutic change. A higher degree of psychological dissociation as a predictor of treatment response was found in several studies, 20 , 85 , 86 while others failed to prove this relationship. 71 , 101 …”
Section: Discussionmentioning
confidence: 92%
“…Psychological dissociation (assessed with DES) did not correlate with the outcome criteria of therapeutic change. A higher degree of psychological dissociation as a predictor of treatment response was found in several studies, 20 , 85 , 86 while others failed to prove this relationship. 71 , 101 …”
Section: Discussionmentioning
confidence: 92%
“…Moreover, recent studies showed that there is a relationship between childhood trauma and the severity of psychiatric disorders, such as anxiety disorder (32), depression (33), psychosis (34), bipolar disorder (35), somatization (36), suicide attempts (37) and conversion disorder (38). On the other hand, although one study detected high OCD scores in individuals with childhood trauma compared to those without it (5), most previous studies of OCD found no significant relationship between childhood trauma and OCD severity (9)(10)(11)(12). Two studies estimated only weak correlations between OCD severity and childhood trauma (2,39), and this was true only for the severity of obsessions in one of them (2).…”
Section: Discussionmentioning
confidence: 99%
“…In another nonclinical sample recruited by Briggs et al (8), the severity of childhood trauma was positively correlated with the severity of obsessive-compulsive symptoms, although this relationship was closely associated with depression and anxiety. Most studies of patients diagnosed with OCD have found no relationship between childhood trauma and OCD severity, although some have detected severer OCD in individuals with a history of trauma history (5,(9)(10)(11)(12). However, the relationship between childhood trauma and the severity of OCD symptoms is unclear.…”
mentioning
confidence: 99%
“…Os pacientes tiveram mais dificuldades no campo das habilidades sociais: fazer e manter amigos, participar de atividades pertinentes a idade (97) comportamentos pró-sociais (98) , comunicação, socialização, ajuste emocional (99) mais medo de avaliações negativas (98) . Além disso, sintomas mais graves de TOC foram associados à vitimização entre pares de acordo com Piacentini, et al, 2003 (97) (50,80,84) . Esse achado lança luz para a importância do estudo desses eventos e do impacto deles na gravidade dos sintomas associados aos transtornos psiquiátricos.…”
Section: Dados Clínicosunclassified
“…Nesse sentido, o fato dos pacientes terem menos fatores relacionados a resiliência, conforme era esperado, foi preditor de maior quantidade comorbidades.A DES, escala que mede experiências dissociativas, foi a melhor preditora tanto dos sintomas ansiosos quanto dos sintomas depressivos nos pacientes. Esse achado vai ao encontro do que tem sido discutido pela literatura, que constatou associação entre experiências dissociativas e gravidade dos sintomas depressivos e SOCs(73,77,79,80,83,84) .Algumas hipóteses são levantadas para explicar porque as experiências dissociativas são um preditor de maior gravidade de sintomas Goff et al (1992) (73). discutem que a presença de dissociação poderia ser um marcador de ansiedade mais grave ou SOCs.…”
unclassified